Perancangan Media Pembelajaran IPA Terpadu Berbasis Computer Assisted Instruction Model Tutorial pada Topik Fotosintesis Menggunakan Adobe Animate CC untuk SMP - Yusuf, Alfi Suryani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
The aim of this paper was to designing a media of integrated science learning on photosynthesis topics based on tutorial models of computer assisted instruction using Adobe Animate CC for Junior High School. Designing process of this media covered several stages, namely the preparation stage, the creation stage using Adobe Animate CC, and the completion stage. This media was stored in files with extension (dot) exe. This learning media of tutorial models CAI consisted of several parts, namely intro, basic competencies and indicators, menus, materials, exercises and developer info. This learning media is useful to support teaching process ofintegrated science learning in junior high school. In addition, this learning media can be used independently by students.